Modelling Materials on the Primary School as the Element for an Improvement of Fine Motor Skills and a Support of Creativity - SIMBARTL, PETR (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2017)
A work with the modelling material is incorporated in the framework education programme even for the nursery school and also for primary schools. The modelling material is incorporated there for the purpose of the output (managing the hand and eye coordination, managing the fine motor skills). The character of the material, incorporation of a working process, aids and tools for modelling is important in the primary school. Thanks to the characters of the modelling masses (material, variety of colours/colouring) are all these outputs fully supported. We deal with different types of modelling doughs and with their possibilities of the use in primary schools and with creativity testing of children.